Smoking, drinking, and depression: comorbidity in head and neck cancer patients undergoing radiotherapy - Kristen McCarter; Amanda L. Baker; Benjamin Britton; Luke Wolfenden; Chris Wratten; Judith Bauer; Sean A. Halpin; Gregory Carter; Alison K. Beck; Lucy Leigh; Christopher Oldmeadow (Cancer Medicine)
Abstract We aimed to determine the prevalence and co‐occurrence of tobacco smoking, alcohol consumption, and depressive symptoms among a sample of head and neck cancer (HNC) patients undergoing radiotherapy. A total of 307 HNC patients participated in a multi‐site stepped‐wedge randomized controlled trial (RCT) evaluating the effectiveness of a dietitian‐delivered health behavior intervention in patients with HNC undergoing radiotherapy. During week one of radiotherapy patients completed measures of smoking, alcohol consumption, and level of depression. Approximately one‐fifth (21%) of patients had two or more co‐occurring problems: current smoking, hazardous alcohol use, and/or likely presence of a major depressive episode (MDE). Approximately one‐third (34%) of the sample were current smokers, one‐third (31%) were drinking hazardously and almost one‐fifth (19%) had likely cases of depression. Comorbidity of smoking, hazardous alcohol use, and MDE is high in HNC patients, and interventions need to address this cluster of cancer risk factors.